From Environment to Profit: The Impact of Green Accounting and Environmental Performance on Financial Performance - Indrayani, Salsa Vonni; Rahayu, Sri; Putra, Wirmie Eka (Jurnal sosial dan sains, 2025)
This study aims to systematically review the empirical literature on the relationship between green accounting and environmental performance with financial performance. Despite growing attention to sustainability practices in corporate management, empirical findings remain inconsistent regarding their economic implications. This inconsistency creates confusion for both academics and practitioners in understanding the true value of environmental initiatives. The primary research problem addressed in this study is the lack of comprehensive synthesis explaining why green accounting and environmental performance show varying effects on financial performance across different contexts. The review was conducted using a Systematic Literature Review (SLR) approach by analyzing 30 relevant articles published within the 2020–2025 period, selected through rigorous inclusion criteria from credible academic journals. The results indicate that both green accounting and environmental performance mostly show insignificant effects on financial performance, with 14 out of 25 studies (56%) finding no significant relationship for green accounting, and 10 out of 22 studies (45%) reporting similar findings for environmental performance. However, some studies documented positive effects when sustainability practices are managed as a corporate strategy to enhance reputation, legitimacy, and competitive advantage. These findings suggest that the economic benefits of environmental management are indirect and influenced by contextual factors such as industry characteristics, regulatory environments, and strategic orientation. The practical implications of this study emphasize that companies must integrate environmental practices into core business strategies rather than treating them as mere compliance activities, while policymakers should consider designing incentive mechanisms that accelerate the transformation of environmental investments into measurable financial returns. This study contributes to a comprehensive understanding of empirical inconsistencies and emphasizes the need for a more strategic sustainability approach to support financial performance.